Dynamics of the Urban Middle Class, Consumerism, Social Mobility and New Identities - Ayu Ramli (Generasi Sains Indonesia, 2025)
The growth of the urban middle class in Indonesia has become one of the most significant social phenomena in the past two decades, reshaping lifestyles, consumption patterns, and identity formation. This study critically examines the dynamics of the urban middle class through three interrelated dimensions: consumerism, social mobility, and the construction of new identities. Using a quantitative survey method with 400 respondents from five major Indonesian cities, data were collected through a Likert-scale questionnaire and analyzed using descriptive statistics, Pearson correlations, and multiple linear regression. The results show that consumerism is strongly embedded in middle-class practices, with high preferences for branded goods and lifestyle consumption, functioning as both status symbols and markers of modernity. Social mobility is primarily associated with education, which respondents consider the most important factor in achieving upward mobility, although structural limitations of the labor market often constrain these aspirations. Identity construction is increasingly mediated by digital platforms, where social media serves as a space for professional representation and urban belonging. Regression analysis reveals that consumerism (β = 0.41) has a stronger influence than social mobility (β = 0.36) in shaping new identities, indicating that lifestyle symbols play a more central role than structural achievements. Overall, the study concludes that the urban middle class embodies both cosmopolitan modernity and structural vulnerability, making it a socially and culturally contested category rather than merely an economic stratum.